The Effect of Local Point Acupuncture Therapy with a Combination of Tamanu Oil (Callophyllum Inophyllum.) on Changes In The Degree of Acne Vulgaris Lesions in Students Of Smait Ibnu Abbas Klaten - Fidiyah, Tazkia Aulia Alif; Wardoyo, Suwaji Handaru; Haryanto, Joko Tri (Indonesian Journal of Acupuncture, 2024)
Acne vulgaris is chronic inflammation of the sebaceous glands which has several types such as comedo, papule, pustule, nodule, and might leave scars in the form of tissue scars. Treatment for acne vulgaris can include acupuncture and the use of herbs. Acupuncture can be done by inserting filiform needles at local point around the acne lesion. Tamanu oil (Callophyllum inophyllum) applied topically to acne lesions can reduce inflammation and speed healing. The aim of this study was to determine the effect of local point acupuncture therapy with a combination of tamanu oil on case of acne vulgaris in female students at SMAIT Ibnu Abbas Klaten